Hakikat Manusia dan Implikasinya bagi Pendidikan: Tinjauan Filosofi Pendidikan Islam (Kajian Literatur) (Equilibrium: Jurnal Pendidikan, 2026)
This study aimed to analyze the nature of humans and their relationship to education from a philosophical perspective, particularly within the framework of Islamic educational philosophy. Humans, as God’s creatures, were understood to possess intellectual, physical, and spiritual potential that needed to be developed holistically through education. In Islamic thought, education was not limited to the transmission of knowledge but also served as a means to cultivate moral integrity and spiritual character, enabling humans to fulfill their role as caliphs on earth. This research employed a literature study method by examining various relevant works to explore the concept of humanity and education in philosophy. The findings highlight that education is a lifelong process which integrates religious and intellectual values, and it is essential for shaping individuals who are responsible to God, society, and the environment.